Subjective health status of the older population: Is it related to country-specific economic development measures? - Teresa García-Mu\~noz; Shoshana Neuman; Tzahi Neuman (Bar-Ilan University, Department of Economics, 2014)
It is now common to use the individual's self-assessed-health-status (SAHS), which expresses her/his holistic internal view, as a measure of health. The use of SAHS is supported by numerous studies that show that SAHS is a better predictor of mortality and morbidity than medical records. The 2011 wave of the rich Survey of Health Aging and Retirement Europe (SHARE) is used for the exploration of the full spectrum of factors behind the health-status in 16 European countries, using about 33 thousand observations. Special emphasis is given to the examination of development country measures and their correlation with aggregate country-levels of subjective-health. The empirical analysis includes 2 layers: (i) estimation of SAHS equations, using a large set of personal socioeconomic characteristics as explanatory variables (controlling for country fixed-effects); and (ii) study of the correlations between average country SAHSs - controlled for differences in populations' socio-economic characteristics - and objective countryspecific aggregate macroeconomic development variables (logarithm of per-capita GDP; the Human Development Index; life expectancy at birth; per-capita expenditures on health; percentage of GDP spent on education; income inequality). The second part of the empirical examination (that borrows the technique used by Oswald and Wu, 2010) is novel and will lead to an answer to our core question: Is subjective-health affected by the country's economic development level? [...]
Keywords: 330